2012
DOI: 10.1038/hr.2012.160
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, study design, baseline characteristics and blood pressure at 16 weeks in the HONEST Study

Abstract: On the basis of the studies that investigated the relationship between baseline clinic blood pressure (CBP) or home blood pressure (HBP) values and cardiovascular (CV) events, HBP has been reported to have a stronger prognostic ability. However, few studies have compared the prognostic ability of on-treatment CBP and HBP. The relationship between on-treatment HBP, measured twice in the morning and twice at bedtime, and CV events was investigated in over 20 000 patients in the HONEST (Home blood pressure measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 29 publications
(28 reference statements)
1
42
0
1
Order By: Relevance
“…Although the 2nd SBP was 2-3 mm Hg lower than the 1st SBP in the population as a whole, about 30% of the patients had 2nd - 1st SBP >0 mm Hg. The results of our study agree with those of the previous studies, in which the mean values of 2nd measurements were 2-3/1-2 mm Hg lower than the mean values of 1st measurements on each occasion [10,11,12,13,14,15,16]. However, the details regarding the differences between the two measurements were not clarified in these previous studies.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although the 2nd SBP was 2-3 mm Hg lower than the 1st SBP in the population as a whole, about 30% of the patients had 2nd - 1st SBP >0 mm Hg. The results of our study agree with those of the previous studies, in which the mean values of 2nd measurements were 2-3/1-2 mm Hg lower than the mean values of 1st measurements on each occasion [10,11,12,13,14,15,16]. However, the details regarding the differences between the two measurements were not clarified in these previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…The European guideline proposes three measurements on each occasion [9]. Many previous studies have shown that the BP of the second measurement was lower than that of the first measurement [10,11,12,13,14,15,16]. However, it is not clear whether this tendency is a consistent finding for each subject over a long period.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…11 HONEST is a large-scale prospective observational study with a 2-year follow-up period and is registered at the UMIN Clinical Trials Registry (http://www.umin.ac.jp/ctr/index.htm) with the unique trial number UMIN000002567.…”
Section: Methodsmentioning
confidence: 99%
“…11 In the present analysis, we used HBP and CBP data from patients receiving antihypertensive treatment to determine their relationship with the incidence of cardiovascular events, which was a primary objective of the HONEST study.…”
mentioning
confidence: 99%